2017
DOI: 10.1186/s12911-017-0420-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of computational modeling for surgical planning of arteriovenous fistula for hemodialysis

Abstract: BackgroundAutogenous arteriovenous fistula (AVF) is the best vascular access (VA) for hemodialysis, but its creation is still a critical procedure. Physical examination, vascular mapping and doppler ultrasound (DUS) evaluation are recommended for AVF planning, but they can not provide direct indication on AVF outcome. We recently developed and validated in a clinical trial a patient-specific computational model to predict pre-operatively the blood flow volume (BFV) in AVF for different surgical configuration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…A patient‐specific hemodynamic computational model, using preoperative ultrasound measurements together with other input variables, has been recently validated to predict the increase in Qa after AVF placement . The clinical use of this computational model may facilitate individualization of the vascular access and a more patient‐centered approach . A collaborative decision‐making process with involvement of cardiologists in the vascular access choice in patients at risk should be strongly considered …”
Section: Future Directionsmentioning
confidence: 99%
“…A patient‐specific hemodynamic computational model, using preoperative ultrasound measurements together with other input variables, has been recently validated to predict the increase in Qa after AVF placement . The clinical use of this computational model may facilitate individualization of the vascular access and a more patient‐centered approach . A collaborative decision‐making process with involvement of cardiologists in the vascular access choice in patients at risk should be strongly considered …”
Section: Future Directionsmentioning
confidence: 99%
“…From recent studies the computational model has been found to reliably predict immediate post-operative blood flows and could therefore be useful for clinical decision support. 12,13,21 Unfortunately, in this randomised clinical trial maturation rates were not improved by providing flow predictions during surgical planning. Despite an overall accurate flow prediction, the FTM rates were around 30% in both groups.…”
Section: Discussionmentioning
confidence: 95%
“…R 2 ¼ .66) in 60 patients for flow prediction at 40 days. 21 This difference can be explained by the controlled study setting in which Caroli et al attained their input, whereas in Bozzetto et al input data was more representative for daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and treatment in TCM are mainly based on syndrome differentiation. Multidisciplinary computational modeling approaches 4348 have become valuable tools for diagnosis, therapy, and prevention of diseases in the clinical setting, but these tools have not been used in TCM syndrome differentiation to date. Because correct syndrome differentiation is fundamental for effective treatment of diseases, this project is being performed to develop an application-oriented, machine-readable TCM Yin–Yang syndrome computer modeling system for cardiovascular disease with the aid of a noninvasive cardiac electrophysiology imaging technique.…”
Section: Tcm Syndrome Computer Modeling Of Heart Palpitationmentioning
confidence: 99%